Systemic inflammation and immune cell phenotypes are associated with neuro‐psychiatric symptoms in patients with chronic inflammatory liver diseases. (12th June 2018) - Aregay, Amare; Dirks, Meike; Schlaphoff, Verena; Owusu Sekyere, Solomon; Haag, Kim; Falk, Christine Susanne; Hengst, Julia; Bremer, Birgit; Schuppner, Ramona; Manns, Michael P.; Pflugrad, Henning; Cornberg, Markus; et al.
Abstract: Background & Aims: Chronic inflammatory liver diseases are frequently associated with neuropsychiatric and cognitive dysfunctions. We hypothesized that symptomatic patients may show altered levels of soluble inflammatory mediators (SIMs) as well as changes in immune cell phenotypes. Methods: A comprehensive immune‐phenotyping including investigation of 50 SIMs as well as ex‐vivo phenotypes of NK‐cells, CD3+, CD4+, CD8+ and regulatory T cells in 40 patients with viral and autoimmune chronic liver diseases was performed. The patients' cognitive functions were assessed using an extensive battery of neuropsychological testing. Results and Conclusion: Overall, our data indicate that while SIMs are significantly up‐regulated, NK‐ and T‐cells are less‐activated in patients with neuropsychiatric symptoms accompanying chronic inflammatory liver diseases compared to patients without these symptoms. Moreover, HCV patients showed a unique pattern of immune alterations as compared to patients with HBV, autoimmune hepatitis and primary biliary cirrhosis. These findings hint towards potential mechanisms explaining these symptoms in patients with chronic liver diseases.